Degradable wound dressing and preparation method thereof

The Janus composite membrane was prepared by electrospinning technology, combining the design of hydrophobic and hydrophilic fiber layers, and solved the shortcomings of wound dressing in anti-adhesion, anti-infection, aging resistance and chemical stability, achieving efficient wound healing effect.

CN119633159APending Publication Date: 2025-03-18WEIHAI WEIGAO FUSEN MEDICAL MATERIALS CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411851726.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Existing wound dressings are difficult to achieve long-term anti-adhesion effect, while effectively preventing infection, taking into account aging resistance and chemical stability.

Method used

An Janus composite membrane was prepared by electrospinning technology. The hydrophobic fiber layer consists of hydrophobic biodegradable polymers and polyphenol compounds. The hydrophilic fiber layer is composed of polyglycolic acid and gelatin, which is loaded with pro-angiogenic drugs.

Benefits of technology

It achieves long-term anti-adhesion effect, effectively prevents infection, has excellent aging resistance and chemical stability, and promotes wound healing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005190758650000011
    Figure HDA0005190758650000011
  • Figure HDA0005190758650000012
    Figure HDA0005190758650000012
  • Figure HDA0005190758650000021
    Figure HDA0005190758650000021
Patent Text Reader

Abstract

The invention belongs to the technical field of medical materials, and particularly relates to a degradable wound dressing and a preparation method thereof. Compared with the prior art, the degradable wound dressing prepared by the preparation method disclosed by the invention is a completely biodegradable Janus composite film, and a hydrophobic inner layer and a hydrophilic outer layer are obtained by selecting different materials; the material PGA with excellent biological performance is utilized, the problem that electrostatic spinning cannot be carried out through pure PGA is solved, PGA and gelatin are creatively mixed, the advantages of PGA and gelatin are combined, and the PGA / Gel electrostatic spinning film which is high in toughness, high in tensile strength, good in biocompatibility and high in medicine carrying efficiency is obtained; meanwhile, the functions of resisting bacteria, resisting inflammation, discharging seepage and promoting angiogenesis are achieved, and the wound healing rate is effectively guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of medical materials, and in particular relates to a degradable wound dressing and a preparation method thereof. Background Art

[0002] The skin is the largest organ in the human body and is the first effective barrier against external pathogens. However, the skin is often easily damaged. One of the key issues of skin damage is bacterial infection, which usually leads to inflammation and even ulceration of the wound. Therefore, dressings with antibacterial properties are needed to avoid bacterial infection. In addition, ideal wound dressings should also have the characteristics of hemostasis, breathability, and non-toxicity. While absorbing wound exudate, they provide a moist environment for the wound and promote wound healing.

[0003] In recent years, electrospinning, as a method of preparing nanofibers by electrospraying, has been widely used in the biomedical field. On the one hand, the nanofiber membrane produced by electrospinning technology has high porosity and large specific surface area, ensuring sufficient air permeability and oxygen permeability, and can mimic the extracellular matrix (ECM) of the skin. On the other hand, in the process of preparing nanofibers, small molecules such as drugs and growth factors that are beneficial to cell behavior can be carried. The release of these specific drugs provides a good environment for cell proliferation and tissue regeneration, which can effectively promote wound repair.

[0004] In the report on the use of electrospun nanofiber membranes for wound dressings, the electrospun Janus nanofiber membrane showed unique advantages. The Janus membrane has an asymmetric structure. Its hydrophobic layer is in direct contact with the wound, isolating it from external moisture and microorganisms, and the hydrophilic layer can highly absorb wound exudate and often carry other bioactive substances. And because the hydrophilicity and hydrophobicity on both sides of the Janus membrane are different, wound exudate can be transported unidirectionally from the hydrophobic side to the hydrophilic side, and the two play their respective roles to promote wound healing. Therefore, the selection of the hydrophobic inner layer and hydrophilic outer layer materials of the Janus membrane and the loading of active substances play a decisive role in the performance of its functions and the characteristics of the membrane.

[0005] Commonly used biodegradable synthetic polymers include polylactic acid-glycolic acid (PLGA), polylactic acid (PLA), poly(ε-caprolactone) (PCL), polyvinylidene fluoride (PVDF), polyglycolic acid (PGA), etc. Among them, PGA is a simple linear structure polyester, a product of human metabolism, with excellent biodegradation and biocompatibility. The degradation products are finally CO2 and H2O, which will not cause any harm to human health. It has shown excellent effects in the fields of medical sutures, fracture fixation materials, tissue engineering repair materials, etc. However, there are few studies on PGA spinning fibers. The main reason is that pure PGA fibers are brittle and have low mechanical strength in the human body. Therefore, in order to take advantage of the advantages of PGA materials for spinning and application in human tissue engineering, it is necessary to blend with other soft materials for modification and toughening. Gelatin is an incomplete hydrolysis product of collagen. It comes from the epidermis of animals. It is cheap and easy to obtain. It has good biocompatibility and degradability. At the same time, gelatin has natural water solubility, good gelling properties, and is easy to chemically modify. It is often used as a carrier for human antibacterial materials. However, gelatin is too hydrophilic and has poor mechanical properties. Mixing PGA and gelatin to spin can overcome the defects of the two materials and obtain a new type of electrospinning membrane material with excellent performance. Summary of the invention

[0006] In view of this, the technical problem to be solved by the present invention is to provide an antibacterial repair device and a preparation method thereof which can achieve long-term anti-adhesion effect, effectively prevent infection, and have excellent aging resistance and chemical stability.

[0007] The present invention provides a method for preparing a degradable wound dressing, comprising the following steps:

[0008] S1) electrospinning a first spinning solution to obtain a hydrophobic fiber layer; the first spinning solution comprises a hydrophobic biodegradable polymer, a polyphenol compound and a first solvent;

[0009] S2) electrospinning a second spinning solution to form a hydrophilic fiber layer on the surface of the hydrophobic fiber layer, and drying to obtain a degradable wound dressing; the second spinning solution includes polyglycolic acid, gelatin, angiogenesis-promoting drug and a second solvent.

[0010] Preferably, the hydrophobic biodegradable polymer is selected from one or more of poly(ε-caprolactone), polyvinylidene fluoride and polylactic acid;

[0011] The polyphenolic compound is selected from one or more of curcumin, tannic acid, anthocyanin, baicalin, eugenol and cinnamon extract;

[0012] The angiogenesis-promoting drug is selected from deferoxamine and / or Dendrobium officinale;

[0013] The first solvent and the second solvent are each independently selected from one or more of hexafluoroisopropanol, N,N-dimethylformamide and dichloromethane;

[0014] The second solvent is selected from hexafluoroisopropanol or a mixed solution of hexafluoroisopropanol and 90% acetic acid.

[0015] Preferably, the mass concentration of the hydrophobic biodegradable polymer in the first spinning solution is 7.2% to 18%;

[0016] The mass concentration of the polyphenol compound in the first spinning solution is 0.05% to 0.5%.

[0017] Preferably, the mass concentration of polyglycolic acid in the second spinning solution is 10% to 50%;

[0018] The mass concentration of gelatin in the second spinning solution is 10% to 50%;

[0019] The concentration of the angiogenesis-promoting drug in the second spinning solution is 10-100 μM.

[0020] Preferably, the first spinning is prepared according to the following method:

[0021] mixing a hydrophobic biodegradable polymer solution with a polyphenol compound solution to obtain a first spinning solution;

[0022] The mass concentration of the hydrophobic biodegradable polymer solution is 8% to 20%;

[0023] The mass concentration of the polyphenol compound solution is 0.5% to 5%;

[0024] The volume ratio of the hydrophobic biodegradable polymer solution to the polyphenol compound solution is (8-9):1.

[0025] Preferably, the injection rate of electrospinning in step S1) is 0.4-1.2 mL / h; the voltage of electrospinning is 10-23 kV; the specification of the electrospinning needle is 20-22 G; and the distance between the needle and the collector during electrospinning is 12-15 cm.

[0026] Preferably, the injection rate of electrospinning in step S2) is 3-8 mL / h; the voltage of electrospinning is 20-25 kV; the specification of the electrospinning needle is 18-22 G; and the distance between the needle and the collector during electrospinning is 20-25 cm.

[0027] Preferably, the electrospinning in step S1) is carried out at a temperature of 20°C to 30°C and a humidity of 42% to 46%; the electrospinning time is 30 to 45 minutes;

[0028] In the step S2), the electrospinning is carried out at a temperature of 20° C. to 30° C. and a humidity of 42% to 46%; the electrospinning time is 30 to 45 minutes.

[0029] The present invention also provides a degradable wound dressing prepared by the above preparation method, comprising a hydrophobic fiber layer and a hydrophilic fiber layer arranged on one surface of the hydrophobic fiber layer; the hydrophobic fiber layer comprises hydrophobic biodegradable polymer fibers; the hydrophobic biodegradable polymer fibers are loaded with polyphenol compounds; the hydrophilic fiber layer comprises polyglycolic acid and gelatin composite hydrophilic fibers; the polyglycolic acid and gelatin composite hydrophilic fibers are loaded with pro-angiogenesis drugs.

[0030] Preferably, the thickness ratio of the hydrophobic fiber layer to the hydrophilic fiber layer is 1:(1-5).

[0031] Compared with the prior art, the present invention has the following advantages:

[0032] 1) The degradable wound dressing prepared by the present invention is a completely biodegradable Janus composite membrane, and a hydrophobic inner layer and a hydrophilic outer layer are obtained by selecting different materials.

[0033] 2) The present invention utilizes PGA, a material with excellent biological properties, to overcome the difficulty that pure PGA cannot be used for electrospinning. PGA is creatively mixed with gelatin to combine the advantages of both, thereby obtaining a PGA / Gel electrospinning membrane with strong toughness, high tensile strength, good biocompatibility and high drug loading efficiency.

[0034] 3) The degradable wound dressing prepared by the present invention directly contacts the wound with the hydrophobic fiber layer carrying polyphenolic compounds, which has direct antibacterial and anti-inflammatory effects without producing cytotoxicity. In addition, the layer is protected by the outer membrane, which can inhibit the inactivation of polyphenolic compounds by light.

[0035] 4) The degradable wound dressing prepared by the present invention has the function of unidirectionally transporting wound exudate due to the different hydrophilic and hydrophobic degrees on both sides, which can trigger the continuous cascade release of the pro-angiogenic drugs in the outer layer to exert their effects, while avoiding the cytotoxicity caused by direct contact of the drugs with the wound surface.

[0036] 5) The degradable wound dressing prepared by the present invention is completely biodegradable, and implements the green and environmentally friendly scientific and technological concept. In addition, if the dressing is not replaced in time, the dressing can degrade by itself, avoiding secondary damage caused by pulling the adhesion wound when changing the traditional dressing.

[0037] 5) The degradable wound dressing provided by the present invention is a new type of wound dressing, which simultaneously realizes the functions of antibacterial, anti-inflammatory, exudate discharge, and angiogenesis promotion, and effectively ensures the wound healing rate. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is a graph of the tensile strength of Janus double-layer dressings J1-J4 obtained in Examples 1 to 4 of the present invention;

[0039] Figure 2 This is a colony counting result diagram of Janus double-layer dressings J1 and J2 obtained in Examples 1 and 2 of the present invention using a plate counting method;

[0040] Figure 3 This is a graph showing the results of measuring the DPPH removal effects of the two Janus double-layer dressings J1 and J2 obtained in Examples 1 and 2 of the present invention;

[0041] Figure 4 This is a graph showing the results of CCK-8 cell proliferation activity identification of the Janus double-layer dressing J2 obtained in Example 2 of the present invention and the Janus double-layer dressing J5 obtained in Example 5. DETAILED DESCRIPTION

[0042] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0043] The present invention provides a method for preparing a degradable wound dressing, comprising the following steps: S1) electrospinning a first spinning solution to obtain a hydrophobic fiber layer; the first spinning solution comprises a hydrophobic biodegradable polymer, a polyphenol compound and a first solvent; S2) electrospinning a second spinning solution to form a hydrophilic fiber layer on the surface of the fiber hydrophobic layer, and drying to obtain a degradable wound dressing; the second spinning solution comprises polyglycolic acid, gelatin, an angiogenesis-promoting drug and a second solvent.

[0044] The present invention has no particular limitation on the sources of all raw materials, and any raw materials available on the market can be used.

[0045] The first spinning solution is subjected to electrostatic spinning to obtain a hydrophobic fiber layer; the first spinning solution comprises a hydrophobic biodegradable polymer, a polyphenol compound and a first solvent; the hydrophobic biodegradable polymer is any hydrophobic biodegradable polymer known to those skilled in the art without any special limitation, and in the present invention, it is preferably one or more of poly(ε-caprolactone) (PCL), polyvinylidene fluoride (PVDF) and polylactic acid (PLA); the weight average molecular weight of the hydrophobic biodegradable polymer is preferably 20000-200000 g / mol, more preferably 50000-150000 g / mol, more preferably 50000-120000 g / mol, more preferably 60000-10000 g / mol. 0g / mol, most preferably 80000g / mol; the polyphenol compound can be a polyphenol compound well known to those skilled in the art without special restrictions, and in the present invention, it is preferably one or more of curcumin, tannic acid, anthocyanin, baicalin, eugenol and cinnamon extract; the first solvent is preferably one or more of hexafluoroisopropanol, N,N-dimethylformamide (DMF) and dichloromethane (DCM), more preferably hexafluoroisopropanol or a mixed solution of N,N-dimethylformamide and dichloromethane; the mass ratio of N,N-dimethylformamide to dichloromethane in the mixed solution of N,N-dimethylformamide and dichloromethane is preferably 1: (7-10), more preferably 1: (8-10), and more preferably 1: (10-15). : 9; the mass concentration of the hydrophobic biodegradable polymer in the first spinning solution is preferably 7.2% to 18%, more preferably 8% to 18%, more preferably 10% to 18%, and most preferably 14% to 18%; the higher the mass concentration of the hydrophobic biodegradable polymer, the larger the fiber diameter, and within this range, a hydrophobic biodegradable polymer fiber with an ideal hydrophobic effect can be obtained; the mass concentration of the polyphenol compound in the first spinning solution is preferably 0.05% to 0.5%, more preferably 0.1% to 0.3%; in the present invention, the first spinning solution is preferably prepared according to the following method: mixing a hydrophobic biodegradable polymer solution with a polyphenol compound solution to obtain a first spinning solution; the hydrophobic biodegradable polymer The mass concentration of the solution is preferably 8% to 20%, more preferably 10% to 18%, and more preferably 10% to 16%; the mass concentration of the polyphenol compound solution is preferably 0.5% to 5%, and more preferably 1% to 3%; the solvents of the hydrophobic biodegradable polymer solution and the polyphenol compound solution are preferably the first solvent; the volume ratio of the hydrophobic biodegradable polymer solution to the polyphenol compound solution is preferably (8 to 9): 1, and more preferably 9: 1; the injection rate of the electrospinning is preferably 0.4 to 1.2 mL / h; within this injection rate range, fibers with suitable diameters can be obtained; in the present invention, the injection rate of the electrospinning is more preferably 0.6 to 1.2 mL / h, and more preferably 0.8 to 1.2mL / h, most preferably 1.0mL / h; the voltage of electrospinning is preferably 10-23kV; within this voltage range, smooth and continuous PCL@Cur fibers can be obtained; in the present invention, the voltage of electrospinning is more preferably 10-20kV, more preferably 10-18kV, and most preferably 10-15kV; the specification of the electrospinning needle is preferably 20-22G; the distance between the needle and the collector during electrospinning is preferably 12-15cm, more preferably 13-15c m, preferably 14-15 cm; the electrospinning is preferably carried out at a temperature of 20°C to 30°C and a humidity of 42% to 46%, more preferably at a temperature of 22°C to 28°C and a humidity of 43% to 45%, more preferably at a temperature of 24°C to 26°C and a humidity of 43% to 45%, most preferably at a temperature of 25°C and a humidity of 44%; the electrospinning time is preferably 30 to 45 min, more preferably 35 to 45 min, and more preferably 40 min. .

[0046] The second spinning solution is electrospun to form a hydrophilic fiber layer on the surface of the hydrophobic fiber layer; the second spinning solution comprises polyglycolic acid, gelatin, angiogenesis-promoting drug and a second solvent; the volume ratio of the first spinning solution to the second spinning solution is preferably 2: (0.5-2), more preferably 2: (0.5-1.5), more preferably 2: (0.8-1.5), and most preferably 2: 1; the mass concentration of polyglycolic acid in the second spinning solution is preferably 10%-50%, more preferably 10%-40%, and more preferably 10%-30%; the weight average molecular weight of the polyglycolic acid is preferably 1×10 5 ~2×10 5 g / mol, more preferably 1.2×10 5 ~1.5×10 5 g / mol, preferably 1.3×10 5 g / mol; the mass concentration of gelatin in the second spinning solution is preferably 10% to 50%, more preferably 10% to 40%, and more preferably 10% to 30%; the weight average molecular weight of the gelatin is preferably 1×10 5 ~3×10 5 g / mol, more preferably 1.5×10 5 ~2.5×10 5 g / mol, preferably 2×10 5g / mol; the angiogenic drug can be any angiogenic drug known to those skilled in the art without any special limitation, and in the present invention, it is preferably deferoxamine and / or Dendrobium candidum; the concentration of the angiogenic drug in the second spinning solution is preferably 10-100 μM, more preferably 50-100 μM; the second solvent is preferably hexafluoroisopropanol or a mixed solution of hexafluoroisopropanol and 90% acetic acid; the mass ratio of hexafluoroisopropanol to 90% acetic acid in the mixed solution of hexafluoroisopropanol and 90% acetic acid is preferably (8-10):1, more preferably 9:1; in the present invention, the second spinning solution is preferably prepared according to the following method: polyglycolic acid is mixed with the second solvent, and then gelatin is added to dissolve, and then the angiogenic drug is added and stirred in the dark to obtain the second spinning solution; the time for stirring in the dark is preferably 0.5-2 h, more preferably 0.8-1.5 h, and more preferably 1 h; the injection rate of the electrospinning is preferably 3-8 mL / h , more preferably 4-6mL / h, and more preferably 5mL / h; the voltage of the electrospinning is preferably 20-25kV, more preferably 22-25kV, more preferably 24-25kV, and most preferably 25kV; the specification of the electrospinning needle is preferably 18-22G, more preferably 20-22G; the distance between the needle and the collector during electrospinning is preferably 20-25cm, more preferably 20-24cm, and more preferably 20-22cm; the electrospinning is preferably carried out at a temperature of 20℃-30℃ and a humidity of 42%-46%, more preferably at a temperature of 22℃-28℃ and a humidity of 43%-45%, more preferably at a temperature of 24℃-26℃ and a humidity of 43%-45%, and most preferably at a temperature of 25℃ and a humidity of 44%; the electrospinning time is preferably 30-45min, more preferably 30-40min, and more preferably 30-35min.

[0047] A hydrophilic fiber layer is formed on the surface of the hydrophobic fiber layer, and the layer is dried to obtain a degradable wound dressing; the drying is preferably vacuum drying; the drying is preferably carried out at room temperature; the drying time is preferably 1 to 5 days, more preferably 2 to 4 days, and even more preferably 3 days.

[0048] The present invention also provides a degradable wound dressing prepared by the above preparation method, comprising a hydrophobic fiber layer and a hydrophilic fiber layer arranged on one surface of the hydrophobic fiber layer; the hydrophobic fiber layer comprises hydrophobic biodegradable polymer fibers; the hydrophobic biodegradable polymer fibers are loaded with polyphenol compounds; the hydrophilic fiber layer comprises polyglycolic acid and gelatin composite hydrophilic fibers; the polyglycolic acid and gelatin composite hydrophilic fibers are loaded with pro-angiogenesis drugs.

[0049] The degradable wound dressing provided by the present invention comprises a hydrophobic fiber layer, which not only has a hydrophobic effect, but also has antibacterial and anti-inflammatory functions; the hydrophobic fiber layer comprises hydrophobic biodegradable polymer fibers; the hydrophobic biodegradable polymer fibers are preferably fibers of one or more of poly(ε-caprolactone), polyvinylidene fluoride fibers and polylactic acid, and more preferably poly(ε-caprolactone) fibers; the hydrophobic biodegradable polymer fibers are loaded with polyphenolic compounds; the polyphenolic compounds are preferably one or more of curcumin (Cur), tannic acid, anthocyanin, baicalin, eugenol and cinnamon extract; the mass ratio of the hydrophobic biodegradable polymer fibers to the polyphenolic compounds is preferably (7.2-18): (0.05-0.5). The hydrophobic fiber layer uses FDA-approved hydrophobic polymer PCL, which has good mechanical properties and excellent spinnability. It is equipped with curcumin (Cur), a natural polyphenol compound with anti-inflammatory, antioxidant and anti-infection properties. While PCL isolates bacteria and transports wound exudate in one direction, Cur further exerts its antibacterial and anti-inflammatory functions, making the lower layer completely antibacterial and highly effective in anti-inflammatory.

[0050] A hydrophilic fiber layer is arranged on one surface of the hydrophobic fiber layer; the hydrophilic fiber layer includes a composite hydrophilic fiber of polyglycolic acid (PGA) and gelatin (Gel); the mass ratio of polyglycolic acid to gelatin in the composite hydrophilic fiber of polyglycolic acid and gelatin is preferably (5-8): (2-5); the hydrophilic fiber layer uses polymer gelatin (Gel) with good hygroscopicity and wound healing function as a carrier material, and the degradable material PGA is used to enhance its mechanical properties; the composite hydrophilic fiber of polyglycolic acid and gelatin is loaded with angiogenesis-promoting drugs; the angiogenesis-promoting drugs are selected from deferoxamine (DFO) and / or Dendrobium officinale.

[0051] In a specific embodiment provided by the present invention, the thickness ratio of the hydrophobic fiber layer to the hydrophilic fiber layer is preferably 1:(1-5), more preferably 1:(2-4), and even more preferably 1:3.

[0052] The degradable wound dressing provided by the present invention comprises a hydrophobic fiber layer and a hydrophilic fiber layer. When in use, the hydrophobic fiber layer is used as the contact surface, i.e., the lower layer. The huge wettability difference between the hydrophobic fiber layer and the hydrophilic fiber layer enables the excessive exudate around the wound surface to be effectively discharged, thereby triggering the continuous cascade release of DFO in the hydrophilic fiber layer (upper layer), exerting angiogenesis-promoting activity, while avoiding the cytotoxicity caused by direct contact of DFO with the wound surface. Natural phenolic drugs are easily photodegraded under artificial or natural sunlight. In this double-layer membrane structure, the bottom fiber membrane containing the drug is protected by the top fiber membrane to avoid photodegradation and inactivation, thereby maximizing its effect.

[0053] In order to further illustrate the present invention, a degradable wound dressing and a preparation method thereof provided by the present invention are described in detail below in conjunction with embodiments.

[0054] The reagents used in the following examples are all commercially available; the Mw of the PCL particles used in the examples is 8×10 4 g / mol; the Mw of PGA powder is 1.3×10 5 g / mol; gelatin used in the example Mw = 2×10 5 g / mol.

[0055] Example 1

[0056] 1.1 Preparation of PCL@Cur fiber hydrophobic layer: Weigh 10.5g PCL particles, use 55mL hexafluoroisopropanol (HFIP) as solvent, add PCL particles to the solvent, and stir magnetically to accelerate dissolution to obtain a uniform PCL spinning solution. Cur is dissolved in HFIP to prepare a Cur solution with a mass fraction of 1wt%. The two prepared solutions are mixed and stirred in a volume ratio of 9:1 to obtain a mixed spinning solution; 10mL of the mixed spinning solution is transferred to a 10mL syringe, a 22G metal needle is used, the injection rate of the spinning solution is set to 1.0mL / h, the voltage is 15kV, the distance between the needle and the collector is controlled at 15cm, and spinning is carried out at room temperature of 25℃ and 44% humidity. The spinning time is 40min, and a PCL@Cur fiber membrane with an area of ​​15cm×15cm and a thickness of 0.2mm is obtained.

[0057] 1.2 Preparation of PGA / Gel@DFO hydrophilic fiber layer and Janus dressing: The spinning of PGA / Gel@DFO fiber layer was carried out on the surface of PCL@Cur fiber layer. First, 8.0 g of PGA powder was weighed and dissolved in 60 mL of hexafluoroisopropanol (HFIP), and then Gel was added thereto to make its mass fraction 10 wt%. Magnetic stirring was used to accelerate the dissolution. Then, 50 μM DFO was added to the solution and stirred for 1 h in the dark. 5 mL of the mixed solution was transferred to a 5 mL syringe. A 22 G metal needle was used to wrap the PCL@Cur fiber hydrophobic layer prepared in the previous step on the roller surface. The injection rate of the spinning solution was set to 5.0 mL / h, the voltage was 25 kV, and the distance between the needle and the collector was controlled at 20 cm. Spinning was carried out at room temperature of 25 ° C and 44% humidity for 30 min. The obtained double-layer electrospun fiber was vacuum dried at room temperature for 3 days to obtain Janus double-layer dressing J1 with a final thickness of 0.8 mm, which was stored in a desiccator for subsequent use.

[0058] Example 2

[0059] 2.1 Preparation of PCL@Cur fiber hydrophobic layer: Weigh 10.5g PCL particles, use 55mL hexafluoroisopropanol (HFIP) as solvent, add PCL particles to the solvent, and stir magnetically to accelerate dissolution to obtain a uniform PCL spinning solution. Cur is dissolved in HFIP to prepare a Cur solution with a mass fraction of 3wt%. The two prepared solutions are mixed and stirred in a volume ratio of 9:1 to obtain a mixed spinning solution. Take 10mL of the mixed spinning solution and transfer it to a 10mL syringe. Use a 22G metal needle. The injection rate of the spinning solution is set to 1.0mL / h, the voltage is 15kV, and the distance between the needle and the collector is controlled at 15cm. Spinning is carried out at room temperature of 25℃ and 44% humidity. The spinning time is 40min, and a PCL@Cur fiber membrane with an area of ​​15cm×15cm and a thickness of 0.2mm is obtained.

[0060] 2.2 Preparation of PGA / Gel@DFO hydrophilic fiber layer and Janus dressing: The spinning of PGA / Gel@DFO fiber layer was carried out on the surface of PCL@Cur fiber layer. First, 8.0 g of PGA powder was weighed and dissolved in 60 mL of hexafluoroisopropanol (HFIP), and then Gel was added thereto to make its mass fraction 10 wt%. Magnetic stirring was used to accelerate the dissolution. Then, 50 μM DFO was added to the solution and stirred for 1 h in the dark. 5 mL of the mixed solution was transferred to a 5 mL syringe. A 22 G metal needle was used to wrap the PCL@Cur fiber hydrophobic layer prepared in the previous step on the roller surface. The injection rate of the spinning solution was set to 5.0 mL / h, the voltage was 25 kV, and the distance between the needle and the collector was controlled at 20 cm. Spinning was carried out at room temperature of 25 ° C and 44% humidity for 30 min. The obtained double-layer electrospun fiber was vacuum dried at room temperature for 3 days to obtain Janus double-layer dressing J2 with a final thickness of 0.8 mm, which was stored in a desiccator for subsequent use.

[0061] Example 3

[0062] 3.1 Preparation of PCL@Cur fiber hydrophobic layer: Weigh 10.5g PCL particles, use 55mL hexafluoroisopropanol (HFIP) as solvent, add PCL particles to the solvent, and stir magnetically to accelerate dissolution to obtain a uniform PCL spinning solution. Cur is dissolved in HFIP to prepare a Cur solution with a mass fraction of 1wt%. The two prepared solutions are mixed and stirred in a volume ratio of 9:1 to obtain a mixed spinning solution; 10mL of the mixed spinning solution is transferred to a 10mL syringe, a 22G metal needle is used, the injection rate of the spinning solution is set to 1.0mL / h, the voltage is 15kV, the distance between the needle and the collector is controlled at 15cm, and spinning is carried out at room temperature of 25℃ and 44% humidity. The spinning time is 40min, and a PCL@Cur fiber membrane with an area of ​​15cm×15cm and a thickness of 0.2mm is obtained.

[0063] 3.2 Preparation of PGA / Gel@DFO hydrophilic fiber layer and Janus dressing: The spinning of PGA / Gel@DFO fiber layer was carried out on the surface of PCL@Cur fiber layer. First, 8.0 g of PGA powder was weighed and dissolved in 60 mL of hexafluoroisopropanol (HFIP), and then Gel was added thereto to make its mass fraction 30 wt%. Magnetic stirring was used to accelerate the dissolution. Then, 50 μM DFO was added to the solution and stirred for 1 h in the dark. 5 mL of the mixed solution was transferred to a 5 mL syringe. A 22 G metal needle was used to wrap the PCL@Cur fiber hydrophobic layer prepared in the previous step on the roller surface. The injection rate of the spinning solution was set to 5.0 mL / h, the voltage was 25 kV, and the distance between the needle and the collector was controlled at 20 cm. Spinning was carried out at room temperature of 25 ° C and 44% humidity for 30 min. The obtained double-layer electrospun fiber was vacuum dried at room temperature for 3 days to obtain Janus double-layer dressing J3 with a final thickness of 0.8 mm, which was stored in a desiccator for subsequent use.

[0064] Example 4

[0065] 4.1 Preparation of PCL@Cur fiber hydrophobic layer: Weigh 10.5g PCL particles, use 55mL hexafluoroisopropanol (HFIP) as solvent, add PCL particles to the solvent, and stir magnetically to accelerate dissolution to obtain a uniform PCL spinning solution. Cur is dissolved in HFIP to prepare a Cur solution with a mass fraction of 3wt%. The two prepared solutions are mixed and stirred in a volume ratio of 9:1 to obtain a mixed spinning solution; 10mL of the mixed spinning solution is transferred to a 10mL syringe, a 22G metal needle is used, the injection rate of the spinning solution is set to 1.0mL / h, the voltage is 15kV, the distance between the needle and the collector is controlled at 15cm, and spinning is carried out at room temperature of 25℃ and 44% humidity. The spinning time is 40min, and a PCL@Cur fiber membrane with an area of ​​15cm×15cm and a thickness of 0.2mm is obtained.

[0066] 4.2 Preparation of PGA / Gel@DFO hydrophilic fiber layer and Janus dressing: The spinning of PGA / Gel@DFO fiber layer was carried out on the surface of PCL@Cur fiber layer. First, 8.0 g of PGA powder was weighed and dissolved in 60 mL of hexafluoroisopropanol (HFIP), and then Gel was added thereto to make its mass fraction 30 wt%. Magnetic stirring was used to accelerate the dissolution. Then, 50 μM DFO was added to the solution and stirred for 1 h in the dark. 5 mL of the mixed solution was transferred to a 5 mL syringe. A 22 G metal needle was used to wrap the PCL@Cur fiber hydrophobic layer prepared in the previous step on the roller surface. The injection rate of the spinning solution was set to 5.0 mL / h, the voltage was 25 kV, and the distance between the needle and the collector was controlled at 20 cm. Spinning was carried out at room temperature of 25 ° C and 44% humidity for 30 min. The obtained double-layer electrospun fiber was vacuum dried at room temperature for 3 days to obtain Janus double-layer dressing J4 with a final thickness of 0.8 mm, which was stored in a desiccator for subsequent use.

[0067] Example 5

[0068] 5.1 Preparation of PCL@Cur fiber hydrophobic layer: Weigh 10.5g PCL particles, use 55mL hexafluoroisopropanol (HFIP) as solvent, add PCL particles to the solvent, and stir magnetically to accelerate dissolution to obtain a uniform PCL spinning solution. Cur is dissolved in HFIP to prepare a Cur solution with a mass fraction of 3wt%. The two prepared solutions are mixed and stirred in a volume ratio of 9:1 to obtain a mixed spinning solution; 10mL of the mixed spinning solution is transferred to a 10mL syringe, a 22G metal needle is used, the injection rate of the spinning solution is set to 1.0mL / h, the voltage is 15kV, the distance between the needle and the collector is controlled at 15cm, and spinning is carried out at room temperature of 25℃ and 44% humidity. The spinning time is 40min, and a PCL@Cur fiber membrane with an area of ​​15cm×15cm and a thickness of 0.2mm is obtained.

[0069] 5.2 Preparation of PGA / Gel@DFO hydrophilic fiber layer and Janus dressing: The spinning of PGA / Gel@DFO fiber layer was carried out on the surface of PCL@Cur fiber layer. First, 8.0 g of PGA powder was weighed and dissolved in 60 mL of hexafluoroisopropanol (HFIP), and then Gel was added thereto to make its mass fraction 10 wt%. Magnetic stirring was used to accelerate the dissolution. Then, 100 μM DFO was added to the solution and stirred for 1 h in the dark. 5 mL of the mixed solution was transferred to a 5 mL syringe. A 22 G metal needle was used to wrap the PCL@Cur fiber hydrophobic layer prepared in the previous step on the roller surface. The injection rate of the spinning solution was set to 5.0 mL / h, the voltage was 25 kV, and the distance between the needle and the collector was controlled at 20 cm. Spinning was carried out at room temperature of 25 ° C and 44% humidity for 30 min. The obtained double-layer electrospun fiber was vacuum dried at room temperature for 3 days to obtain Janus double-layer dressing J5 with a final thickness of 0.8 mm, which was stored in a desiccator for subsequent use.

[0070] Example 6

[0071] 6.1 Preparation of PCL@Cur fiber hydrophobic layer: Weigh 10.5g PCL particles, use 55mL hexafluoroisopropanol (HFIP) as solvent, add PCL particles to the solvent, and stir magnetically to accelerate dissolution to obtain a uniform PCL spinning solution. Cur is dissolved in HFIP to prepare a Cur solution with a mass fraction of 3wt%. The two prepared solutions are mixed and stirred in a volume ratio of 9:1 to obtain a mixed spinning solution; 10mL of the mixed spinning solution is transferred to a 10mL syringe, a 22G metal needle is used, the injection rate of the spinning solution is set to 1.0mL / h, the voltage is 15kV, the distance between the needle and the collector is controlled at 15cm, and spinning is carried out at room temperature of 25℃ and 44% humidity. The spinning time is 40min, and a PCL@Cur fiber membrane with an area of ​​15cm×15cm and a thickness of 0.2mm is obtained.

[0072] 6.2 Preparation of PGA / Gel@DFO hydrophilic fiber layer and Janus dressing: The spinning of PGA / Gel@DFO fiber layer was carried out on the surface of PCL@Cur fiber layer. First, 8.0 g of PGA powder was weighed and dissolved in 60 mL of hexafluoroisopropanol (HFIP), and then Gel was added thereto to make its mass fraction 30 wt%. Magnetic stirring was used to accelerate the dissolution. Then, 100 μM DFO was added to the solution and stirred for 1 h in the dark. 5 mL of the mixed solution was transferred to a 5 mL syringe. A 22 G metal needle was used to wrap the PCL@Cur fiber hydrophobic layer prepared in the previous step on the roller surface. The injection rate of the spinning solution was set to 5.0 mL / h, the voltage was 25 kV, and the distance between the needle and the collector was controlled at 20 cm. Spinning was carried out at room temperature of 25 ° C and 44% humidity for 30 min. The obtained double-layer electrospun fiber was vacuum dried at room temperature for 3 days to obtain Janus double-layer dressing J6 with a final thickness of 0.8 mm, which was stored in a desiccator for subsequent use.

[0073] The performance of the Janus double-layer dressing obtained in Examples 1 to 6 was tested as follows:

[0074] Mechanical properties test

[0075] Take J1-J4 to test its tensile properties. The stress-strain curve of each group of fiber membranes was measured using a tensile tester, and the tensile properties (Young's modulus) results were obtained as shown in the figure. Figure 1 The fiber sample was cut into 1×5 cm strips for stretching, and the stretching speed of the instrument was set to 5 mm / min.

[0076] Antibacterial performance test

[0077] The two dressings J1 and J2 were used as the experimental group, and the non-woven fabric was used as the control group. The plate count method was used to verify the antibacterial properties of the dressings. The fiber membrane was cut into a circular sheet material with a diameter of 8 mm and 10 6 50 μL of PBS solution of Staphylococcus aureus (S. aureus) with CFU / mL was added to the surface of each group of samples and incubated in a 37°C incubator for 5 hours. After that, the samples were plated, cultured and counted. The bacterial plate results of non-woven fabrics, J1 and J2 and the statistical results of bacterial survival rates were obtained as shown in the figure. Figure 2 shown.

[0078] Anti-inflammatory properties test

[0079] The two dressings J1 and J2 were selected as the experimental group, and the non-woven fabric was selected as the control group. The DPPH free radical scavenging ability was used as the ROS scavenging ability of the sample, that is, the basis for judging the anti-inflammatory performance. The fiber samples were cut into 1×2 cm rectangular pieces and placed in 5 mL centrifuge tubes. 3 mL of 50 μM DPPH-ethanol solution was added to the centrifuge tubes and incubated in the dark. The DPPH-ethanol solution was taken at 120 min and its absorbance at 510 nm was measured with a UV-visible spectrophotometer to obtain the DPPH free radical scavenging effect of the dressing. Figure 3 As shown, Figure 3 The UV absorption spectra of DPPH-ethanol solution in the presence of different samples (120 min), where the lower the absorbance, the stronger its ROS scavenging ability.

[0080] Cytotoxicity

[0081] The J2 and J5 dressings were selected as the experimental group, and the non-woven fabric was selected as the control group. The samples were cut into circular pieces with the same diameter as the diameter of the 24-well plate, placed at the bottom of the plate, and irradiated with ultraviolet light in a biosafety cabinet for 30 minutes. 4 Each well was inoculated onto the sample surface, and CCK-8 cell proliferation activity was identified at 1d, 2d, and 3d. The results of the identification of the CCK-8 cell proliferation activity of the dressing were obtained as follows: Figure 4 shown.

[0082] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a degradable wound dressing, characterized in that: The following steps are involved: S1) electrospinning a first spinning solution to obtain a hydrophobic fiber layer; the first spinning solution comprises a hydrophobic biodegradable polymer, a polyphenol compound and a first solvent; S2) electrospinning a second spinning solution to form a hydrophilic fiber layer on the surface of the hydrophobic fiber layer, and drying to obtain a degradable wound dressing; the second spinning solution includes polyglycolic acid, gelatin, angiogenesis-promoting drug and a second solvent.

2. The preparation method according to claim 1, characterized in that: The hydrophobic biodegradable polymer is selected from one or more of poly(ε-caprolactone), polyvinylidene fluoride and polylactic acid; The polyphenolic compound is selected from one or more of curcumin, tannic acid, anthocyanin, baicalin, eugenol and cinnamon extract; The angiogenesis-promoting drug is selected from deferoxamine and / or Dendrobium officinale; The first solvent and the second solvent are each independently selected from one or more of hexafluoroisopropanol, N,N-dimethylformamide and dichloromethane; The second solvent is selected from hexafluoroisopropanol or a mixed solution of hexafluoroisopropanol and 90% acetic acid.

3. The preparation method according to claim 1, characterized in that: The mass concentration of the hydrophobic biodegradable polymer in the first spinning solution is 7.2% to 18%; The mass concentration of the polyphenol compound in the first spinning solution is 0.05% to 0.5%.

4. The preparation method according to claim 1, characterized in that: The mass concentration of polyglycolic acid in the second spinning solution is 10% to 50%; The mass concentration of gelatin in the second spinning solution is 10% to 50%; The concentration of the angiogenesis-promoting drug in the second spinning solution is 10-100 μM.

5. The preparation method according to claim 1, characterized in that: The first spinning is prepared according to the following method: mixing a hydrophobic biodegradable polymer solution with a polyphenol compound solution to obtain a first spinning solution; The mass concentration of the hydrophobic biodegradable polymer solution is 8% to 20%; The mass concentration of the polyphenol compound solution is 0.5% to 5%; The volume ratio of the hydrophobic biodegradable polymer solution to the polyphenol compound solution is (8-9):

1.

6. The preparation method according to claim 1, characterized in that: The injection rate of the electrospinning in step S1) is 0.4-1.2 mL / h; the voltage of the electrospinning is 10-23 kV; the specification of the electrospinning needle is 20-22 G; and the distance between the needle and the collector during electrospinning is 12-15 cm.

7. The preparation method according to claim 1, characterized in that: The injection rate of the electrospinning in step S2) is 3-8 mL / h; the voltage of the electrospinning is 20-25 kV; the specification of the electrospinning needle is 18-22 G; and the distance between the needle and the collector during electrospinning is 20-25 cm.

8. The preparation method according to claim 1, characterized in that: In the step S1), the electrospinning is carried out at a temperature of 20°C to 30°C and a humidity of 42% to 46%; the electrospinning time is 30 to 45 minutes; In the step S2), the electrospinning is carried out at a temperature of 20° C. to 30° C. and a humidity of 42% to 46%; the electrospinning time is 30 to 45 minutes.

9. A degradable wound dressing prepared by the preparation method according to any one of claims 1 to 8, characterized in that: It comprises a hydrophobic fiber layer and a hydrophilic fiber layer arranged on one surface of the hydrophobic fiber layer; the hydrophobic fiber layer comprises hydrophobic biodegradable polymer fibers; the hydrophobic biodegradable polymer fibers are loaded with polyphenol compounds; the hydrophilic fiber layer comprises polyglycolic acid and gelatin composite hydrophilic fibers; the polyglycolic acid and gelatin composite hydrophilic fibers are loaded with pro-angiogenesis drugs.

10. The degradable wound dressing according to claim 9, characterized in that: The thickness ratio of the hydrophobic fiber layer to the hydrophilic fiber layer is 1:(1-5).

Citation Information

Cited By

  • Permeability-selective double-sided anisotropic electrostatic spinning membrane, graft, preparation method and application

    CN120361295A

  • Multifunctional electrospinning material, application of multifunctional electrospinning material, artificial blood vessel and preparation method of artificial blood vessel

    CN121428735A